Proceedings IEEE Conference on Industrial Automation and Control Emerging Technology Applications
DOI: 10.1109/iacet.1995.527552
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and performance of variable reluctance (VR) torque coupler

Abstract: A simple analytical method is developed to calculate the torque of P.M.N.R. (hybrid) torque coupler, referred as variable reluctance (V.R.) coupler. The performance of V.R. torque coupler is compared with a P.M. coupler under idealised conditions. The nonlinear effects such as leakage, fringing and saturation are ignored.A series of V.R. couplers were experimentally tested and their performance reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…14 shows that the maximum torque occurs for a large value of β ≃ 0.8, which corresponds to a small opening angle for the salient-pole (20%) compared to the PMs pole-arc to pole pitch ratio (83%). This result is in agreement with a previously published paper about reluctance magnetic couplings [11]. When the salientpole opening becomes very small (i.e.…”
Section: Influence Of Geometrical Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…14 shows that the maximum torque occurs for a large value of β ≃ 0.8, which corresponds to a small opening angle for the salient-pole (20%) compared to the PMs pole-arc to pole pitch ratio (83%). This result is in agreement with a previously published paper about reluctance magnetic couplings [11]. When the salientpole opening becomes very small (i.e.…”
Section: Influence Of Geometrical Parameterssupporting
confidence: 93%
“…However, in the next section, it will be shown that neglecting the magnetic saturation is not an issue, because the optimal shape of the salient poles corresponds to an unsaturated condition for the studied example. The second hypothesis implies using rare‐earth PMs (NdFeB or SmCo), but this is necessary to obtain good performances in terms of torque density [11].…”
Section: 2d Semi‐analytical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen, the torque varies almost sinusoidally with the load angle δ with a period equal to π/ p and a peak value T max that corresponds to the pull‐out torque. This is a classical result for reluctance‐type actuators [10].…”
Section: 3d Finite Element Modellingmentioning
confidence: 74%
“…Among classical magnetic couplings technologies, reluctance torque magnetic couplings have received very little attention in the literature [10,11]. Yet, it can be a good option when one of the mechanical shafts has to be placed in high temperature environment where permanent magnets cannot be used [11].…”
Section: Introductionmentioning
confidence: 99%